Speaking of That: Terms to Avoid or Reconsider in the Eating Disorders Field. Issue 4 (28th March 2016) - Weissman, Ruth S.; Becker, Anne E.; Bulik, Cynthia M.; Frank, Guido K.W.; Klump, Kelly L.; Steiger, Howard; Strober, Michael; Thomas, Jennifer; Waller, Glenn; Walsh, B. Timothy
Abstract: Inspired by an article on 50 terms that, in the interest of clarity in scientific reasoning and communication in psychology, psychiatry, and allied fields, "should be avoided or at most be used sparingly and only with explicit caveats, " 1 we propose a list of terms to avoid or think twice about before using when writing for the International Journal of Eating Disorders (IJED) . Drawing upon our experience as reviewers or editors for the IJED, we generated an abridged list of such terms. For each term, we explain why it made our list and what alternatives we recommend. We hope that our list will contribute to improved clarity in scientific thinking about eating disorders, and that it will stimulate discussion of terms that may need to be reconsidered in our field's vocabulary to ensure the use of language that is respectful and sensitive to individuals who experience an eating disorder. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:349–353)